Inovação e informação - Luiz Claudio Junqueira Henrique (2006)
Information flows feeding an incremental product innovation and variables affecting the behavior of information search have been described through case studies accomplished in three medium-sized industries. Based on the model of market knowledge competenceconstructed by Li & Calantone (1998), which attempts to validate concepts initially developed by Kohli & Jaworski (1993), a new descriptive model was conceived that encompasses (i) the conception of an innovation task, (ii) its redefinition by those responsible for carrying outsuch a task, and (iii) the behavior of those searching for information for both the conception of this innovation task and its implementation. Interviews with company leaders and other players directly involved in the development of new product were made. Data collecting have also included a scrutiny of internal documents and other sources external to the companies in question. Additionally, all interviewees were requested to fill out a questionnaire designed to assess innovative competences within the organization (FRANÇOIS et al, 1999). The present study has concluded that conceiving an objective innovation task is modeled by the company leaders sensemaking a process which affects the selection of information sources and is affected by this selection itself as well. Therefore, the construct of Kohli & Jaworski (1993) for market orientation ends up in a guide for competitors and/or consumers and/or newtechnologies. The consumer orientation has shown to be the least significant among the companies studied. The orientation adopted by the time of conceiving the objective innovation task also affects the choice of information sources, duration and number of cycles of information search as well as the kind of information to be searched. As for the accomplishment of the redefined task, the information search behavior is associated with the fulfillment of predefined routines related to industrial engineering and launching and trading of products.